A preface to Romans : notes on the Epistle in its literary and cultural setting - Bryan, Christopher, 1935- (Oxford University Press, 2000)
Bryan approaches St. Paul's letter to the Romans with a number of aims in view. First, he wants to show which literary type or genre would have been seen by Paul's contemporaries as being exemplified in the letter. He also determines what we can surmise of Paul's attitude and approach to the Jewish bible. The study involves discussion of and comparison with other literature from Paul's time, place and milieu - including other writings attributed to Paul.